Investigation of the Distribution of Orthodontic Anomalies Among Patients in the Eastern Anatolia Region - Akbulut, Yasin (Aves, 2020)
Objective:This study aimed to identify dental anomalies according to Angle's classification, skeletal anomalies according to Steiner's classification, and crowding regions in 2145 patients who presented for consultation at the Department of Orthodontics in the Faculty of Dentistry at Firat University and to determine the distribution of orthodontic anomalies in the Eastern Anatolia Region. Methods:In this study, anamnesis forms based on the radiographic and clinical examinations of 2145 patients with ages ranging from 6 to 29 years and who applied at the University were were evaluated their skeletal anomalies were classified according to Steiner's classification and dental anomalies were classified according to Angles classification. Results:Of the 2145 patients, 373 (64%) were women and 772 (36%) were men. For skeletal anomaly classification, anomalies in 1377 (64.2%) patients were classified as Class I, 569 (26.5%) as Class II, and 199 (9.3%) as Class III. For dental anomaly classification, anomalies in 957 (44.6%) patients were classified as Class I, 962 (44.8%) as Class II, and 226 (10.5%) as Class III. The distributions of these anomalies were also investigated in terms of age, sex, and crowding region. Conclusion:In this sample of the Turkish population consisting of orthodontics patients in the Eastern Anatolia Region, statistically significant differences were observed in terms of age-skeletal and age-dental anomalies.
Keywords: Orthodontic anomaly; Angle's classification; crowding; prevalence; Turkish population